Α-Fetoprotein. Issue 4 (25th May 2011) - Murray, M J; Nicholson, J C
Abstract : α-Fetoprotein (AFP) measurements have clinical implications in fetal medicine and, in infants and older children, in detection, differential diagnosis and monitoring of malignant disease. Maternal serum AFP levels constitute part of a multiple-marker test used in early second-trimester screening to predict risk of fetal chromosomal abnormalities. Those individuals with increased risk are offered further definitive diagnostic investigation. Second-trimester screening is now increasingly being superseded by first-trimester screening with other serum markers and ultrasound. As AFP is only produced physiologically during fetal development, elevated serum levels after the first two post-natal years usually indicate the presence of a malignant disease process. Before this time, levels may be purely physiological and therefore serial values should be plotted on a logarithmic chart to ensure that they are falling appropriately, with a typical half-life of ∼5-6 days. If not, further investigation should be undertaken. Serum AFP is raised in a significant proportion of germ cell tumours (GCTs), hepatoblastoma and hepatocellular carcinoma (HCC). In suspected cases of GCT, serum human choriogonadotropin (HCG) estimation should also be performed. For possible intracranial GCTs, both serum and cerebrospinal fluid levels of AFP and HCG should be measured, ideally before neurosurgical biopsy. In malignant conditions, serum AFP may be used for diagnosis, treatment monitoring, surveillance for disease recurrence and prognostication. Immunohistochemistry for AFP using antibody staining is routinely used to assist pathological diagnosis on tissue sections where the differential includes GCT, hepatoblastoma and/or HCC. Elevations of serum AFP also occur in non-malignant conditions such as chronic liver disease.